The factors of patient‐reported readiness for hospital discharge in patients with depression: A cross‐sectional study - Wang, Mengmeng; Wang, Ya; Meng, Na; Li, Xiaolin (Journal of psychiatric and mental health nursing, 2021)
Accessible summary What is known on the subject? The attributes of readiness for hospital discharge (RHD) have been identified to be physical stability, adequate support, psychological ability, and adequate information and knowledge. Patient‐reported RHD has been regarded as an outcome indicator, and poor RHD leads to unplanned readmission, emergency department visits and even death. Knowledge regarding patient‐reported RHD and its factors among patients with depression is limited. What the paper adds to existing knowledge? RHD among patients with depression is at a moderate level. More than a quarter of people with depression had low RHD. The knowledge dimension of the RHDS among patients with depression should be further strengthened. The length of stay, content received and delivery dimensions of the QDTS were significantly associated with RHD. What are the implications for practice? This study encourages nurses to assess patient‐reported RHD at discharge in mental health settings. Nurses should pay more attention to patients with hospital stays longer than 20 days. Nurses could improve RHD by enhancing the quality of discharge teaching, particularly the content received and the skills nurses used to deliver such content. Nurses’ managers could develop programmes to improve teaching skills via Internet technology, such as simulated patients and online interprofessional discharge planning. Introduction Low readiness for hospital discharge (RHD) can be followed by negative healthcare outcomes. However, no studies have investigated RHD among patients with depression. Aim This study aimed to examine patient‐reported RHD and its factors among patients with depression. Method In total, 367 inpatients with depression were recruited and completed the Readiness for Hospital Discharge Scale (RHDS) and Quality of Discharge Teaching Scale (QDTS). A binary logistic regression analysis was performed to explore the factors of RHD among patients with depression. Results The total RHDS score was 7.70 ± 1.52. Approximately 28.9% of the participants had low RHD (RHDS score < 7). The results revealed that RHD was significantly associated with the length of stay, content received and delivery. Discussion RHD among patients with depression is at a moderate level. More than a quarter of people with depression had low RHD. To improve RHD, enhancing the quality of discharge teaching is imperative for patients with depression. Implications for Practice Nurses should pay more attention to patients with a hospital stay longer than 20 days. Nurses could improve RHD by enhancing the quality of discharge teaching, particularly the content received and the skills nurses used to deliver such content.